Unauthorised access physical penetration testing for IT security teams - Allsopp, Wil.; Safari eBooks (Chichester, West Sussex, U.K. : Wiley, 2009)
"Featuring a Foreword written by world-renowned hacker Kevin D. Mitnick and lead author of The Art of Intrusion and The Art of Deception, this book is the first guide to planning and performing a physical penetration test. Inside, IT security expert Wil Allsopp guides you through the entire process from gathering intelligence, getting inside, dealing with threats, staying hidden (often in plain sight), and getting access to networks and data"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Computer security -- Testing; Computer networks -- Security measures; Electronic books